THE THEORY OF EXISTENCE IN THE TEACHINGS OF YAKUB CHARKHI (Scientific journal of the Fergana State University, 2026)
This article provides a comprehensive analysis of Ya‘qub Charkhī’s philosophical and metaphysical views on existence, based on his major works - “Risāla-yi Qudsiyya,” “Risāla-yi Hurū’iyya,” and “Sharḥ Asmā’ al-Ḥusnā.” The mystic’s interpretation of existence reveals the deepest layers of Sufi metaphysics, shedding light on divine manifestations, the spiritual essence of being, and the stages of the human journey toward spiritual perfection. Ya‘qub Charkhī, following the spiritual and ethical principles of Bahā’uddin Naqshband, further develops the doctrine of waḥdat al-wujūd and compares it with the profound metaphysical ideas of Ibn ‘Arabī’s school.